Da lama à sala de aula : a festa do mastro de Capela/SE narrada em uma HQ para o ensino de história - Macedo, Alexsandro do Nascimento (2021)
The festivals have occupied an expressive place in Brazilian culture, through which social experiences are (re)updated, ritualized and celebrated. The present work aims to enable students in the final years of elementary school to understand the Capela-SE Mast Festival as an event that is the result of a historical construction, through an interdisciplinary analysis. To understand the dynamics and history of this festival, we carried out a field research in 2019, we dialogued with some religious leaders in the municipality, we carried out a survey of photographic records among former residents and participants of the festival, we paid attention to the legislation involving the Festival of the Capela-SE Mast at the municipal and state levels and we analyzed police reports registered during the June period at the Capela-SE Police Station between 2007 and 2017. Our proposal, after the initial survey of information about this cultural manifestation , was to proceed with the creation of a full script script that culminated in the production of a comic book to be used in the classroom. About the history of Festa do Mastro and the role of festivities, we are theoretically anchored in the considerations of Mary Del Priore (1994), Luiz da Câmara Cascudo (2001), Edelice Couto (2001), Jisélia Santos and Denilsa Santos (2014). With regard to the use of Local History in the classroom, we decided to pay attention to what researchers Marcos Martins (2010), Maria Auxiliadora Schimidt (2007) and Circe Bittencourt (2009) say. We point out that the articulation between the objects of knowledge brought by BNCC and what is part of the students' experience, such as the Capela-SE Mast Festival, can make them understand concepts, problematize and understand their reality, bringing meaning to own History and making students realize that they are subjects of their time.